Genomic dynamics of clinical Plasmodium vivax: comparative genomic hybridization in severe malaria cases - Tahbildar, Sampreeti; Boopathi, Pon Arunachalam; Kochar, Sanjay Kumar; Kochar, Dhanpat Kumar; Aiyaz, Mohamed; Mugasimangalam, Raja C.; Rao, Sudha N.; Das, Ashis (Frontiers in Malaria, 2025)
BackgroundCopy number variations (CNVs) in the Plasmodium vivax genome can influence key parasite traits such as erythrocyte invasion, immune evasion, drug resistance, and survival in the human host. Their potential role in severe manifestations of P. vivax malaria, such as cerebral malaria (CM) remains underexplored. In regions like India, where P. vivax is endemic, understanding genomic factors that contribute to disease severity is crucial. Given the limited understanding of genomic factors contributing to disease severity in P. vivax, this study aims to investigate genome-wide CNVs in clinical isolates from patients with cerebral and uncomplicated malaria.MethodsWe employed a high-resolution, custom-designed 2 × 400K tiling microarray for array-based comparative genomic hybridization (aCGH), using probes with an average spacing of 56 base pairs covering the entire P. vivax genome. Genomic DNA from cerebral malaria isolates was differentially labeled and hybridized against reference DNA from uncomplicated malaria isolates. CNVs were inferred based on fluorescence intensity ratios, indicating chromosomal regions with copy number gains or losses.ResultsUtilizing probes based on the P. vivax Sal-1 reference genome, we detected significant CNVs across all 14 chromosomes, affecting 2,138 genes. CNVs ranged from 100 bp to approximately 1,429 kb in cerebral malaria isolates compared to uncomplicated cases. Altered regions having gains or losses included genes encoding surface antigens such as 6-cysteine proteins, tryptophan-rich antigens (TRAGs), serine-repeat antigen (SERA), apical membrane antigen (AMA), as well as drug resistance markers. The most extensive CNV spanned ~1,450 kb on chromosome 12. CNVs were also observed in intergenic regions, suggesting potential regulatory impacts.DiscussionThis study identifies CNVs in the genome of P. vivax isolates from cerebral malaria cases, in genes involved in immune evasion, drug resistance, and host-pathogen interactions. Although the precise impact of these CNVs on disease severity remains unclear, the findings highlight genetic differences between isolates from severe and uncomplicated malaria cases, including variations in intergenic regions. These findings emphasize the need to further investigate CNVs that may contribute to P. vivax pathogenesis and resistance. A deeper understanding of these variations could aid in identifying biomarkers for severe disease and support the development of more effective malaria control and treatment strategies.